Short Text Message Based Infusion Fluid Level Monitoring System - Safitri, Meilia; Da Fonseca, Helena; Loniza, Erika (Journal of Robotics and Control (JRC), 2021)
Liquids or medications administered through intravenous systems (infusion) is necessary when a patient requires immediate medication or requires slowly and continuously administered medications. This method is considered adequate in certain situations; however, the liquids/medications administration of through infusion has a risk when the nurse is late in replacing intravenous fluid. In this study, the system was designed to monitor the fluid infusion level by utilizing a short text message system. This system will provide information when the infusion fluid level is at 50 ml, 20 ml, and 0 via SMS. Moreover, a buzzer is utilized that acts as an alarm when the reaching 20 ml level, and infusion fluid have not been replaced yet, and when the intravenous fluid does not drip. Infra-red sensors and photodiodes are used to detect intravenous droplets of fluid, which are then used to calculate fluids' volume. The system is controlled using an Atmega 328 microcontroller. SIM Modem 900 is used to send SMS. Based on tests carried out, infusion fluid level monitoring systems have excellent performance. The percentage of system errors when detecting fluid level infuse is 1,21%. The function of sending fluid level information through SMS also works well